2020
DOI: 10.1111/jcmm.16047
|View full text |Cite
|
Sign up to set email alerts
|

circRNA 001306 enhances hepatocellular carcinoma growth by up‐regulating CDK16 expression via sponging miR‐584‐5p

Abstract: The incidence is rising faster than that for any other cancer in both men and women, and the 5-year survival rate is less than 18%. 1 Hepatocellular carcinoma (HCC) is a type of primary liver cancer, which is accounting for approximately 90% of liver cancer. Most HCC patients were diagnosed at the advanced stages, missing the best treatment time, which seriously affected the survival time of patients. 2 Thus, finding the method or marker for early diagnosis is important for prognosis of HCC. Circular RNAs (cir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…19 , 33 , 34 , 35 , 36 Increasing studies showed that circRNAs involved in the development of many diseases including cancers, neurological diseases, congenital diseases, intervertebral disc degeneration and endocrine diseases. 37 , 38 , 39 , 40 , 41 , 42 , 43 Recently, studies indicated that circRNAs also play important roles in osteoporosis. 44 …”
Section: Introductionmentioning
confidence: 99%
“…19 , 33 , 34 , 35 , 36 Increasing studies showed that circRNAs involved in the development of many diseases including cancers, neurological diseases, congenital diseases, intervertebral disc degeneration and endocrine diseases. 37 , 38 , 39 , 40 , 41 , 42 , 43 Recently, studies indicated that circRNAs also play important roles in osteoporosis. 44 …”
Section: Introductionmentioning
confidence: 99%
“…It has been widely revealed that circRNAs are of vital importance in biological functions of various cancers through interacting with miRNAs, which can serve as ceRNAs [ 10 12 ]. For example, the upregulated circ_001306 could enhance cell proliferation of HCC through interacting with miR-584-5p/CDK16 signaling pathway [ 10 ]. Therefore, we analyzed the potential downstream miRNAs of circ_0067835, which illustrated that miR-1236-3p might be one of them.…”
Section: Discussionmentioning
confidence: 99%
“…Covalently bound CDK inhibitors can usually achieve higher activity and selectivity, leading to longer-lasting therapeutic effects and a possible reduction in serious side effects. The first of these inhibitors to be synthesized was THZ1 (43), which contains an N-phenyl-pyrimidin-2-amine backbone, the common core of many potent kinase inhibitors, such as imatinib. 172 The primarily hydrophobic binding pocket of CDK7, which originally accommodates the bound ATP, is occupied by 43.…”
Section: Launched and Clinical Cdk Inhibitorsmentioning
confidence: 99%